FOURIER SERIES APPLICATION FOR MODELING “CHOCOLATE” KEYWORD SEARCH TRENDS IN GOOGLE TRENDS DATA - Andrea Tri Rian Dani; Fachrian Bimantoro Putra; Muhammad Aldani Zen; Vita Ratnasari; Qonita Qurrota A'yun (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2023)
In some cases of regression modeling, it is very common to find a repeating pattern. To model this, of course, the approach used must be in accordance with the characteristics of the data. The Fourier series is one of the proposed approaches, because it has advantages in modeling relationship patterns that tend to repeat, such as cosine sine waves. The Fourier series is a subset of nonparametric regression, which has good flexibility in modeling. In this study, the Fourier series approach was applied to model search trend data for the keyword